Vertex Metric-Based Dimension of Generalized Perimantanes Diamondoid Structure - Hamdan Alshehri; Ali Ahmad; Yahya Alqahtani; Muhammad Azeem (IEEE Access, 2022)
Due to its superlative physical qualities and its beauty, the diamond is a renowned structure. While the green-colored perimantanes diamondoid is one of a higher diamond structure. Motivated by the structure’s applications and usage, we look into the metric-based parameters of this structure. In this draft, we have discussed metric dimension and their generalizations for the generalized perimantanes diamondoid structure and proved that each parameter depends on the copies of original or base perimantanes diamondoid structure and changes with the parameter ${n}$ or its number of copies.